The imperfective in subjunctive conditionals: fake or real aspect? - Martin, Fabienne (Proceedings of the Amsterdam Colloquium, 2015)
This paper aims to provide a ‘real aspect’ approach of the ‘fake’ imperfective in subjunctive conditionals and a new account of the (non)-cancellability of the counterfactual inference in SCs, largely based on Ippolito 2013. It is argued that PAST and PRES above MODAL in conditionals compete the same way as in non-modal stative sentences, see Altshuler and Schwarzschild 2012. On this view, the counterfactual inference of SCs, when cancellable, is nothing else than the cessation implicature routinely triggered by past stative sentences.